Proteomic study of soybean and nematode interaction (The Journal of Plant Protection Sciences, 2022)
Soybean (Glycine max) is the second largest  crop in the United States. The annual loss of  soybean due to various diseases is approxi mately 2 billion dollars in the U.S. (1). Soy bean cyst nematode (SCN), Heterodera gly cines, is the major pathogen of soybean and  was responsible for approximately $ 500 mil lion in losses in 2010. Some soybean acces sions have resistance to certain isolates of cyst  nematode, but none are resistant to all iso lates. To gain new insights into the mecha nism of soybean interaction with the SCN and  to further develop the resistant varieties,  knowledge of genomics and proteomic of the  nematode is important. To devise strategies to  control SCN and develop soybeans with broad  resistance against SCN, basic information  about the nematode’s proteome would provide  a better understanding of SCN parasitism and  its virulence.
Keywords: Genomic; several proteins